2007
DOI: 10.1055/s-2007-990288
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin, TNF-α and IL-6 mRNA Expression is Increased in Mononuclear Cells from Type 2 Diabetic Women

Abstract: Visfatin, is a new adipokine, highly expressed in the visceral fat of both mice and humans. To examine whether visfatin is expressed in human peripheral monocyte-enriched mononuclear cells and whether its expression is altered in type 2 diabetes (DM2), we compared 24 DM2 women [17 overweight (BMI >25) and 7 lean (BMI<25)] to 26 healthy women (14 overweight and 12 lean), all premenopausal. Relative visfatin mRNA levels were significantly higher (approximately 3-fold) in DM2 compared to healthy control women (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
5
31
3
Order By: Relevance
“…Our study provides evidence that obese patients exhibit upregulated NAMPT mRNA expression levels in PBC, contrasting with previously published results where a negative or no correlation with BMI was detected [39,46]. However, a positive correlation has been shown with waist circumference measures, a better indicator of visceral obesity [46]. The lack of association between the circulating concentrations and the mRNA expression levels of NAMPT in PBC, omental adipose tissue and liver suggests that other organs or cell types, including bone marrow or muscle [11], may be contributing to the increased NAMPT levels in obesity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study provides evidence that obese patients exhibit upregulated NAMPT mRNA expression levels in PBC, contrasting with previously published results where a negative or no correlation with BMI was detected [39,46]. However, a positive correlation has been shown with waist circumference measures, a better indicator of visceral obesity [46]. The lack of association between the circulating concentrations and the mRNA expression levels of NAMPT in PBC, omental adipose tissue and liver suggests that other organs or cell types, including bone marrow or muscle [11], may be contributing to the increased NAMPT levels in obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…The dimerization of visfatin may have functional implications, particularly in regard to its NADþ biosynthetic enzyme function that has been shown to depend on dimerization and to be active also in the extracellular space [44]. Our study provides evidence that obese patients exhibit upregulated NAMPT mRNA expression levels in PBC, contrasting with previously published results where a negative or no correlation with BMI was detected [39,46]. However, a positive correlation has been shown with waist circumference measures, a better indicator of visceral obesity [46].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The G allele or GG genotype in the IL-6 gene promoter region (-174), was associated with high IL-6 production in TB patients which may have promoted TB by inhibiting production of other cytokines like TNF and IL-1β which was dissimilar to our study where GG genotype was associated with low IL-6 production in PTB patients [43,44]. Selvaraj et al, has not reported any significant association between the genotypes of IL-6 -174G>C polymorphisms and production both in PTB and HCs unlike our study population [45]. Studies have not been reported in TBDM, TBDM HHC, PTB HHC and DM.…”
Section: Discussioncontrasting
confidence: 99%
“…16,17 Some evidence in humans indicates that obesity and insulin resistance are associated with activation of these cells and with changes in the expression of a variety of cytokines related to inflammation and the immune response, such as interleukin-6 and tumor necrosis factor-a. 15,18,19 Moreover, PBMC express molecules related with energy homeostasis that are altered in the obese state, such as leptin, visfatin and resistin, [20][21][22] and their expression profile responds to differences in nutrient status. 23,24 Several gene expression studies using microarray analysis have assessed a differential expression in genetically and diet-induced obese animals, but most of them explored adipose tissue.…”
Section: And Ginter and Simkomentioning
confidence: 99%